The Relationship Between Study Anxiety and Academic Performance among Engineering Students - Muhammad Nubli, Abdul Wahab; Vitasari, Prima; Ahmad, Othman; Herawan, Tutut; Suriya Kumar, Sinnadurai (Elsevier, 2010)
Anxiety is one of the major predictors of academic performance. Students with anxiety disorder display a passive attitude in their studies such as lack of interest in learning, poor performance in exams, and on assignments. This research observes the relationship between study anxiety level and students’ academic performance. The test to find out a significant correlation of anxiety and academic performance was has carried out among engineering students. A total 205 males and females student participated in this test. They were second year students from four engineering faculties at Universiti Malaysia Pahang (UMP).The study anxiety level was measured using State Trait Anxiety Inventory (STAI). Meanwhile, students’ academic performance was measured using Grade Point Average (GPA). The results showed that there was a significant correlation of high level anxiety and low academic performance among engineering students, with significant correlation (p=0.000) and the correlation coefficient is small with r=-.264. Large of sample size required to strengthen the coefficient correlation was suggested for further research.